(untitled) (Research, Society and Development, 2020)
Objective: To report the experience of a nursing student regarding the difficulties faced by the CIHDOTT / OPO team during communication between the nurse and the family in the process of organ and tissue donation for transplants. Methodology: This is a descriptive, exploratory study of the type of experience report in a Hospital and Emergency Room located in the eastern part of the city of Manaus - Amazonas. Results: Communication represents the primary element for the nurse’s interaction with the family, which provides awareness of the importance of donation. However, several factors contribute negatively to this, such as the lack of knowledge of some health professionals in the hospital and society about the theme. Conclusion: The need for a greater approach on Brain Death and the stages of the organ donation process during graduation was highlighted, as well as training courses on communication with professionals and bad news to family members.